Evaluation of image velocimetry for the quantification of discharge and characterization of the flow in the Pilcomayo River with acoustic profilers - Patalano, Antoine (2020)
The Pilcomayo River basin is shared by three countries: Argentina, Bolivia and Paraguay, which rises great challenges socially, economically and environmentally. First, from the social point of view, there are more than 20 ethnic groups living in the basin area. Second, economic demand is high in this region although the river basin is located far away from the major economic centers in each country. Environmentally several aspects can be considered. In the upper basin mining and oil-gas activities have been intense for centuries. In the middle basin the river has a high lateral mobility and sediment transport from the higher basin to the lower one gives the river a characteristic behavior of stream blockage which leads to the formation of various wetlands with high biodiversity. This second edition presents a compilation and analysis of major hydraulic problems encountered in the basin. These problems involve the high mobility of the channel, the possibility of changing course during floods, and serious difficulties in the distribution of water and sediment between Argentina and Paraguay.